The host mannose-6-phosphate pathway and viral infection - Liu, Qincheng; Wang, Weiqi; Xu, Liwei; Zhang, Qisheng; Wang, Hongna (Frontiers in Cellular and Infection Microbiology, 2024)
Viruses, despite their simple structural composition, engage in intricate and complex interactions with their hosts due to their parasitic nature. A notable demonstration of viral behavior lies in their exploitation of lysosomes, specialized organelles responsible for the breakdown of biomolecules and clearance of foreign substances, to bolster their own replication. The man-nose-6-phosphate (M6P) pathway, crucial for facilitating the proper transport of hydrolases into lysosomes and promoting lysosome maturation, is frequently exploited for viral manipulation in support of replication. Recently, the discovery of lysosomal enzyme trafficking factor (LYSET) as a pivotal regulator within the lysosomal M6P pathway has introduced a fresh perspective on the intricate interplay between viral entry and host factors. This groundbreaking revelation illuminates unexplored dimensions of these interactions. In this review, we endeavor to provide a thorough overview of the M6P pathway and its intricate interplay with viral factors during infection. By consolidating the current understanding in this field, our objective is to establish a valuable reference for the development of antiviral drugs that selectively target the M6P pathway.